Fuzzy quadratic programming model for the optimal design of an algal bioenergy park under optimal price markdown percentage - Ubando, Aristotle T. (Animo Repository, 2017)
Algae bioenergy park offers an efficient solution in producing algal bioproducts while increasing the industrial park's efficiency and profit while reducing its wastes and environmental emissions. An industrial park consists of multiple interdependent industries with potentially shared material and energy flow streams. Its inherent complexity of interconnectivity of streams make the design of an industrial park challenging. This study proposes a fuzzy quadratic programming model for the optimal design of an algal bioenergy park which comprised of an integrated microalgae-biodiesel plant, an ethanol plant, a cement factory, a sugar mill with power production, and a poly(β-hydroxybutyrates) and methanol plant. The system was designed based on satisfying multiple objectives such as meeting product demand limits, maximizing tenant annual profits, and minimizing environmental footprints. The study includes the impact of the optimal markdown pricing percentage as a price-break strategy in the design of an algae bioenergy park. The results indicate the feasibility of the proposed optimal design of the algae bioenergy park. It also have shown a 2.33% increase in the overall degree of satisfaction at the optimal markdown pricing percentage of 75%. Overall, the study can serve as a reference in the application of markdown pricing as a business strategy in companies under industrial symbiosis. © 2016 IEEE.